Margem Esquerda n. 41 - REA, Editor (Revista Espaço Acadêmico, 2023)
Margem Esquerda n. 41 Entrevista: Nancy Fraser Dossiê: Terra arrasada Autores: Artur Renzo, Beluce Bellucci, Bruna Della Torre, Carlos Vainer, Cássio Arruda Boechat, Fabiano Escher, Fernando Garcia, Flávia Braga Vieira, Flávio Wolf de Aguiar, Gabriel S. Figueiredo, Igor Palma Barbosa, Jean Tible, João Felipe de Almeida Ferraz, João Pedro Inácio Peleja, João Quartim de Moraes, Jorge O. Romano, José Paulo Netto, Leonilde Servolo de Medeiros, Luiz Felipe Osório, Marco Gonsales, María Julia Giménez, Maria Lygia Quartim de Moraes, Marta Nehring, Murillo van der Laan, Nathalie Bressiani, Paulo F. Petersen, Thiago Lima Ensaio visual: Gabriela Fero (com curadoria de Francisco Klinger) Editora Boitempo, 2023, 160 p.